Biomechanical Analysis of Key Kinematic Variables During the Release Phase in Medium-Pace Cricket Bowling (A Comprehensive Structural Equation Model) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Cricket is not solely about scoring runs; bowling plays a crucial role in achieving overall team success. Among the various types of bowling, medium-pace bowling is one of the most challenging and essential skills to master. Accuracy is a key factor in determining the success of a pace bowler in modern cricket, and multiple factors can influence it. Therefore, this study focused on the biomechanical analysis of the release phase in medium-pace bowling to better understand these influencing factors.A total of 30 medium-pace bowlers were selected using the purposive sampling method from cricket academies in Gwalior, Madhya Pradesh. To assess bowling accuracy, the Richard Aldworth Stretch Pace Bowling Test was employed. The entire process was captured using video analysis, and the data collected were analyzed using Structural Equation Modeling (SEM) with the aid of SPSS AMOS 23 software. The results showed that, during the release phase, the angle of the right shoulder (0.048), right hip (0.079), and left wrist (0.007) explained 49% of the variance in predicting the center of gravity, outperforming other variables examined. Additionally, the angles of the right ankle (0.023), right elbow (0.010), and left ankle (0.036) accounted for approximately 42% of the variance in predicting bowling accuracy during the release phase. These findings highlight the importance of specific joint angles in enhancing bowling performance and accuracy in medium-pace bowling.